The Interaction of Protein S with the Phospholipid Surface Is Essential for the Activated Protein C-independent Activity of Protein S - Wijnen, Merel van; Stam, Jeanette G; van't Veer, Cornells; Meijers, Joost C M; Reitsma, Pieter H; Bertina, Rogier M; Bouma, Bonno N (Thrombosis and Haemostasis, 1996)
Protein S is a vitamin-K dependent glycoprotein involved in the regulation of the anticoagulant activity of activated protein C (APC). Recent data showed a direct anticoagulant role of protein S independent of APC, as demonstrated by the inhibition of prothrombinase and tenase activity both in plasma and in purified systems. This anticoagulant effect of protein S can be explained either by a direct interaction of protein S with one of the components of the complexes and/or by the interference with the binding of these components to phospholipid surfaces.During our investigation we noted that protein S preparations purified in different ways and derived from different sources, expressed discrepant APC cofactor and direct anticoagulant activity. In order to elucidate these differences and to study the mechanism of the APC-inde-pendent activity of protein S, we compared the protein S preparations in phospholipid-binding properties and anticoagulant activity. The dissociation constant for the binding of protein S to immobilized phospholipids ranged from 7 to 74 nM for the different protein S preparations. APC-independent inhibition of both prothrombinase and tenase activity performed on phospholipid vesicles and in plasma showed a strong correlation with the affinity for phospholipids. The APC-independent activity could be abolished by monoclonal antibodies that were either calcium-dependent and/or directed against epitopes in the Gla-region of protein S, suggesting that the protein S-phospholipid interaction is crucial for the APC-independent anticoagulant function of protein S. Protein S preparations with a low APC-independent activity expressed a high APC-cofactor activity suggesting that the affinity of protein S for phospholipids is of less importance in the expression of APC-cofactor activity of protein S.We conclude that high affinity interactions of protein S with the membrane surface are essential for the direct anticoagulant activity of protein S and we suggest that inhibition of the prothrombinase and the tenase complex by protein S is a consequence of the occupation of the phospholipid surface by protein S molecules.